AMPLIFICATION FACTORS FOR SPECTRAL ACCELERATION IN TECTONICALLY ACTIVE REGIONS - Stewart J.P.; Choi Y.; Liu A.H. (My University, 2003)
Empirical relationships are developed to predict amplification factors for 5% damped response spectral acceleration (period range T = 0.01-5 sec) as a function of site category. We evaluate amplification factors by normalizing response spectral accelerations computed from recordings by reference spectral accelerations derived from a modified attenuation relationship for active regions. Strong motion sites are categorized according to several schemes, which are based on surface geology (age-only, age + depositional environment, and age + material texture), shallow (30 m) shear-wave velocity, and geotechnical data. Criteria for selection of the optimal classification scheme are that the amplification models for categories within the scheme (1) minimize the global dispersion of prediction residuals and (2) are significantly distinct across a broad period range. The results of the regressions indicate that the greatest levels of distinction in amplification levels across categories occur for the shallow shear-wave velocity scheme, but that the dispersion of residuals for this scheme are relatively high for soil sites (although not for rock sites). Conversely, schemes based on detailed surface geology generally have the smallest dispersion for soil sites, but amplification levels across Quaternary categories are only significantly distinct at small periods. These findings suggest that detailed surface geology provides an effective means of soil site categorization at small periods, whereas shallow shear-wave velocity provides an effective means for rock site categorization at small periods. At longer periods, none of the schemes are optimized relative to both the dispersion and distinction criteria. The principal application of the amplification factors is as a modifier of attenuation relations (much like a site term). The present results significantly reduce the bias associated with the site terms in a widely used attenuation relationship for rock and soft soil site conditions.